Smoothing and derivative calculation of FT-IR spectra of coal by a modified least squares - Alciaturi, C.E.; Escobar, M.E. (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
Fourier-Transform infrared spectroscopy (FT-IR) is an important method for the study of the structure of carbonaceous materials, such as coal, coke, carbon black, active carbon, and pitch. Smoothing and derivative calculation are routinely used for the interpretation of spectra. Here we show the results of applying a least-squares procedure with osculating polynomials to obtain a mathematical model of the infrared spectra of coals, useful for smoothing, band resolution, peak finding, and data compression.